Role Reversal & the Emergence of Househusband in Adichie’s The Visit - Onyekachi Peter Onuoha; Lilian Onyinye Ohanyere (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2021)
Creative literature is a site for possibilities and imagining of society through the portrayal of realities. This study through the application of feminism examines role reversal in Adichie’s The Visit. It further accounts for the emergence of the househusband which many creative writers and scholars have failed to account for. This study observes that sex and its function in African literature are related to gender and it is performative. This study claims that matriarchy is as oppressive as patriarchy and that economic privileges and social mobility are tools for the subjugation of sexes in marriage. This study concludes that for the first time, there is a deliberate depiction of the power of the woman.